The Challenges Faced by Muslim Female Students in Maintaining Appearance and Validity of Wudhu: A Study on the Use of Waterproof Makeup - Ilmi, Maharani Nurul; Rahmani, Ridha Ariandini; Dwi Yanti, Teni; Faqihuddin, Achmad (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2024)
This study examines the challenges faced by Muslim female students in maintaining their physical appearance while ensuring the validity of their ablution (wudhu), specifically regarding the use of waterproof makeup. A qualitative approach was employed, combining a literature review and survey data collected from 23 Muslim female respondents. The results reveal that most respondents prefer regular makeup over waterproof makeup, with 56.5% disliking waterproof makeup and 43.5% using it infrequently. A significant portion of participants expressed inconsistency in removing makeup, particularly mascara, before performing wudhu, with 60.9% uncertain about the implications of not removing makeup. Despite the benefits of waterproof makeup in terms of longevity, most respondents favoured products that are easier to remove for the sake of convenience during wudhu, although they acknowledged the need for touch-ups afterward. Furthermore, 87% of respondents were aware that wudhu is invalid if water does not reach the skin, and 95.7% recognised the importance of removing waterproof makeup to ensure valid wudhu. These findings highlight the difficulties Muslim female students face in balancing appearance with religious obligations. Abstrak: Studi ini menyoroti tantangan yang dihadapi oleh mahasiswi Muslim dalam menjaga penampilan fisik mereka sambil memastikan keabsahan wudhu, khususnya terkait penggunaan makeup waterproof. Penelitian ini menggunakan metode kualitatif dengan kajian pustaka dan pengumpulan data melalui survei yang disebarkan menggunakan Google Form. Sebanyak 23 responden yang merupakan mahasiswi Muslimah berpartisipasi dalam survei ini. Hasilnya mengungkapkan bahwa sebagian besar responden lebih menyukai riasan biasa daripada riasan tahan air, dengan 56,5% tidak menyukai riasan tahan air dan 43,5% jarang menggunakannya. Sebagian besar peserta menyatakan ketidakkonsistenan dalam menghapus riasan, terutama maskara, sebelum berwudhu, dengan 60,9% tidak yakin tentang implikasi dari tidak menghapus riasan. Terlepas dari manfaat riasan tahan air dalam hal keawetan, sebagian besar responden lebih menyukai produk yang lebih mudah dihapus demi kenyamanan selama berwudhu, meskipun mereka mengakui perlunya sentuhan ulang setelahnya. Lebih lanjut, 87% responden menyadari bahwa wudhu tidak sah jika air tidak mengenai kulit, dan 95,7% mengakui pentingnya menghapus riasan tahan air untuk memastikan wudhu yang sah. Temuan ini menyoroti kesulitan yang dihadapi siswi Muslim dalam menyeimbangkan penampilan dengan kewajiban agama.